2017
DOI: 10.1063/1.4973746
|View full text |Cite
|
Sign up to set email alerts
|

The first-principles investigations on magnetic ground-state in Sm-doped phenanthrene

Abstract: Based on the density functional theory plus the effective Coulomb repulsion U, we have investigated the crystal structure, electronic properties and magnetic characteristics in Sm-doped phenanthrene, recently characterized as a superconductor with Tc∼5−6 Kelvin. Calculated total energies of different magnetic states indicate that Sm-doped phenanthrene is stable at the ferromagnetic ground-state. Considered the strong electronic correlations effect due to the intercalation of Sm-4f electrons, we found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…So far, the highest T c reached is 33.1 K in PAH superconductors, which was obtained in K-doped 1,2;8,9-dibenzopentacene . However, previous theoretical studies showed that PAH superconductors usually exhibit the antiferromagnetic (AFM) ground state and exist the strong electronic correlation effects, indicating that the superconducting mechanism is complicated in aromatic hydrocarbons. Our theoretical predictions have argued that electronic correlations or pressure could enhance high T c in aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the highest T c reached is 33.1 K in PAH superconductors, which was obtained in K-doped 1,2;8,9-dibenzopentacene . However, previous theoretical studies showed that PAH superconductors usually exhibit the antiferromagnetic (AFM) ground state and exist the strong electronic correlation effects, indicating that the superconducting mechanism is complicated in aromatic hydrocarbons. Our theoretical predictions have argued that electronic correlations or pressure could enhance high T c in aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%